2020
DOI: 10.3389/fmars.2020.614237
|View full text |Cite
|
Sign up to set email alerts
|

Mate Choice Contributes to the Maintenance of Shell Color Polymorphism in a Marine Snail via Frequency-Dependent Sexual Selection

Abstract: Natural color polymorphisms are widespread across animal species and usually have a simple genetic basis. This makes them an ideal system to study the evolutionary mechanisms responsible for maintaining biodiversity. In some populations of the intertidal snail Littorina fabalis, variation in shell color has remained stable for years, but the mechanisms responsible are unknown. Previous studies suggest that this stability could be caused by frequency-dependent sexual selection, but this hypothesis has not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 115 publications
(132 reference statements)
1
37
0
1
Order By: Relevance
“…Besides speciation being the main focus of the evolutionary research carried out in these species (e.g. Morales Although there are alternative explanations (see Taborsky et al 2009), assortative mating in simple organisms such as marine gastropods is presumably caused by mate choice (Ng et al 2019;Estévez et al 2020). On the other hand, negative assortative mating is directly related to negative-frequency dependent selection, as it has been shown both theoretically (Pusey and Wolf 1996;Hedrick et al 2016 and and empirically in several species (Takashi and Hori 2008;Field and Barrett 2012;Holman et al 2013;Hedrick et al 2016 andEstévez et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Besides speciation being the main focus of the evolutionary research carried out in these species (e.g. Morales Although there are alternative explanations (see Taborsky et al 2009), assortative mating in simple organisms such as marine gastropods is presumably caused by mate choice (Ng et al 2019;Estévez et al 2020). On the other hand, negative assortative mating is directly related to negative-frequency dependent selection, as it has been shown both theoretically (Pusey and Wolf 1996;Hedrick et al 2016 and and empirically in several species (Takashi and Hori 2008;Field and Barrett 2012;Holman et al 2013;Hedrick et al 2016 andEstévez et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, we can say that sexual selection is not contributing to the maintenance of the band polymorphism. The way data were obtained for L. fabalis inEstévez et al (2020) allowed us to estimate this component of natural selection, and we found nor a pattern of NFDS using sexual fitness (females: F 1,7 = 0.53, p =0.497| males: F 1,7 = 0.66, p = 0.452) nor…”
mentioning
confidence: 83%
“…Mating pairs and unmated individuals of L. fabalis were collected from the Fucus spp. canopy in a rocky shore located in Abelleira, A Coruña, NW Spain (42°48′0.30″N-9°1′14.87″W), for a period of 7 years from 2011 to 2017 (see further details in Estévez et al, 2020). The density of the population is relatively large compared with other populations, with tens of individuals per algae.…”
Section: Original Samplingmentioning
confidence: 99%
See 2 more Smart Citations